MIL Cities and MIL Citizens: Informed, Engaged, Empowered by Media and Information Literacy (MIL). - Grizzle, Alton; Jaakkola, Maarit; Durán-Becerra, Tomás; Arroio, Agnaldo; Audenhove, Leo Van; Ballon, Pieter; Bonami, Beatrice; Brennan, Deborah; Den Broeck, Wendy Van; Browne, Harry; Burton, Patrick; Cabello, Patricio; et al. (Corporación Universitaria Minuto de Dios - UNIMINUTO, 2022)
The UNESCO UNITWIN Cooperation Programme on Media and Information Literacy and Intercultural Dialogue (MILID) is based on an initiative from the United Nations Educational, Scientific and Cultural Organization (UNESCO) and the UN Alliance of Civilizations (UNAOC). This Network was created in line with UNESCO’s mission and objectives, as well as the mandate of UNAOC, to serve as a catalyst and facilitator helping to give impetus to innovative projects aimed at reducing polarization among nations and cultures through mutual partnerships. This UNITWIN Network is composed of universities from different geographical areas: Autonomous University of Barcelona (Spain), University of the West Indies (Jamaica), Cairo University (Egypt), University of Sao Paulo (Brazil), Temple University (USA), Tsinghua University (China), Moulay Ismail University (Morocco), Sidi Mohamed Ben Abdellah University (Morocco), University of Guadalajara (Mexico), Western University (Canada), University of Gothenburg (Sweden), Sorbonne Nouvelle University (France), Punjabi University, Patiala (India), University of the South Pacific (Fiji), University of South Africa (South Africa), Nnamdi Azikiwe University (Nigeria), Ahmadu Bello University (Nigeria), Lagos State University (Nigeria), University of Jors (Nigeria), University of Calabar (Nigeria), Hosei University (Japan), University of Latvia (Latvia), Moscow Pedagogical State University (Russia), Corporación Universitaria Minuto de Dios UNIMINUTO (Colombia), Vytautas Magnus University (Lithuania), MICA (India), University of Campinas (Brazil). The main objectives of the Network are to foster collaboration among member universities, to build capacity in each of the countries in order to empower them to advance media and information literacy and intercultural dialogue, and to promote freedom of speech, freedom of information and the free flow of ideas and knowledge. Specific objectives include acting as an observatory for the role of media and information literacy (MIL) in promoting civic participation, democracy and development as well as enhancing intercultural and cooperative research on MIL. The programme also aims at promoting global actions related to MIL and intercultural dialogue. In such a context, a MILID Yearbook series is an important initiative. This MILID Yearbook is a result of a collaboration between UNESCO UNITWIN Cooperation Programme on Media and Information Literacy and Intercultural Dialogue, The Corporación Universitaria Minuto de Dios - UNIMINUTO (Colombia) and the University of Gothenburg (Sweden).
Libro completo
Keywords: Media development; Media and information literacy; Knowledge; Intercultural dialogue